NON-ALCOHOLIC FATTY LIVER DISEASE AND ASSOCIATED CHANGES IN SERUM HEPCIDIN, IRON, FERRITIN-R LEVELS AND TOTAL IRON BINDING CAPACITY IN WEANING WISTAR RATS (RATTUS NORVEGICUS) - A. S. Abbas1 M. H. Abbasi; Ihtzaz A. Malik3and N. Sheikh (Journal of Animal and Plant Sciences, 2014)
The purpose of the present experimental study was to analyze the impact of fat induced NAFLD and fat reducing agents on iron metabolism. Four groups (n=10) of weaning Rattus norvegicus (30g) were designated as Con (Control), I, II, and III.  For 16 weeks Con group was fed on 100% rat chow, I, II and III were provided with diet ‘’A’’ (20% Sucrose + 33% Nestle tea whitener + 34% ground pallet diet +13% water). The diets of group II and III were provided with 5% Nigella sativa and 5% Plantago ovata husk as supplements respectively. After keeping the animals under experimental conditions for 16 weeks, serum samples were taken to analyze iron metabolism related parameters. In comparison with Con group significant changes were observed in the serum hepcidin, iron, ferritin-R levels and Total iron binding capacity of experimental groups. Conclusively, we can say that serum hepcidin, iron and ferritin-R concentrations as well as total iron binding capacity are associated with NAFLD. N. Sativa and P. ovata have impact on iron regulation in diet induced NAFLD.
Keywords: Ferritin-R; Hepcidin; NAFLD; TIBC. N. sativa seeds; P. ovata husk